2003
DOI: 10.1002/pca.727
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the study of C‐glycosyl flavones by ion trap HPLC‐PAD‐ESI/MS/MS: application to seeds of quince (Cydonia oblonga)

Abstract: Ion trap HPLC-PAD-ESI/MS/MS has been used to study C-glycosyl flavones in quince seeds. Comparative analysis of the ions [(M-H)-60]-, [(M-H)-90]- and [(M-H)-120]- from 6-C- and 8-C-glycosyl flavone isomers, together with their respective retention times, allowed deductions to be made about the nature of the sugar units and the positions of C-glycosylation. Vicenin-2 (6,8-di-C-glucosyl apigenin), lucenin-2 (6,8-di-C-glucosyl luteolin), stellarin-2 (6,8-di-C-glucosyl chrysoeriol), isoschaftoside (6-C-arabinosyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
235
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(264 citation statements)
references
References 14 publications
29
235
0
Order By: Relevance
“…30 The loss of À120 mu is typical of C-attached hexoses, whereas that of À90 mu is observed for C-attached pentoses and it is also usual in the case of 6-C-hexoses but less common in the case of Table 3 Retention time (R t ), wavelengths of maximum absorption in the UV-vis region (l max ), pseudomolecular and MS 2 fragment ions (in brackets, relative abundances), tentative identification and quantification of phenolic compounds in wild Arenaria montana 8-C-hexoses. 31 These observations allowed the tentative identication of peak 2 as apigenin 6-C-hexoside-8-C-pentoside. The fragmentation of peak 4 would be more coherent with an O,C-diglycoside.…”
Section: Composition In Hydrophilic Compoundsmentioning
confidence: 88%
“…30 The loss of À120 mu is typical of C-attached hexoses, whereas that of À90 mu is observed for C-attached pentoses and it is also usual in the case of 6-C-hexoses but less common in the case of Table 3 Retention time (R t ), wavelengths of maximum absorption in the UV-vis region (l max ), pseudomolecular and MS 2 fragment ions (in brackets, relative abundances), tentative identification and quantification of phenolic compounds in wild Arenaria montana 8-C-hexoses. 31 These observations allowed the tentative identication of peak 2 as apigenin 6-C-hexoside-8-C-pentoside. The fragmentation of peak 4 would be more coherent with an O,C-diglycoside.…”
Section: Composition In Hydrophilic Compoundsmentioning
confidence: 88%
“…The sugar in the C-glycosyl flavonoid always connects to the 6-C or 8-C with the carbon-carbon band, so compound 1 was a 6,8-di-glycosyl flavonoid. Peak 5 0 was tentatively identified as di-C-hexosyl-pentosyl flavonoid, and fragment ion at m/z 365 and 335 might result from simultaneous rupture of two sugars [34]. MS characterization showed that the flavonoid glycoside in D. odorifera are C-glycosyl flavonoids.…”
Section: Identication Of Flavonoid Glycosides In D Odorifera By Uplcmentioning
confidence: 98%
“…Taking compound 1 0 as an example, the MS spectrum showed the [M1H] 1 at m/z 597, and its MS 2 spectrum is shown in Fig. 5 , respectively, which are produced by cleaving at two sugars simultaneously [33,34]. Many fragment ions produced by combining the loss of H 2 O and the cleavage in the sugar were found in MS 2 spectrum ( Table 2).…”
Section: Identication Of Flavonoid Glycosides In D Odorifera By Uplcmentioning
confidence: 99%
“…The ion at m/z 353 has been associated to apigenin aglycone bearing some sugar residues (270 + 83 u) that remained attached to it (Ferreres et al, 2003;. Although the identity of the hexoside moieties cannot be established, they might be well associated as being glucose.…”
Section: Flavonesmentioning
confidence: 99%
“…This type of compounds is characterized by the loss of characteristics fragments from the cleavage of the sugar pyrano ring, namely -120 u and 90 u in the case hexosides (Ferreres et al, 2003).…”
Section: Flavonesmentioning
confidence: 99%